A study on the dissemination effectiveness and influencing factors of short videos in scientific journals: An empirical analysis based on the ELM model - Sirui Li; Shufang Zhao; Xi Wang; Zhengzong Huang; Xiangdong Liu (PLoS ONE, 2026)
Based on data analysis of 4,422 short videos from scientific journals, this study constructs a Dissemination Effectiveness Index comprising Likes, comments, Favorites, and shares. Using an Enhanced Logistic Model (ELM), it examines how different cues influence dissemination performance. Results indicate that video duration and visual quality show significant positive correlations with dissemination effectiveness, while subtitles and clear covers exert stable effects. The impact direction of Hashtags varies depending on usage patterns. Fan base size and content volume exhibit strong correlations with dissemination effectiveness, demonstrating significant moderating effects across several content characteristics. The study further reveals the limited relevance of verification badges, reflecting evolving trends in platform recommendation and user selection mechanisms. Interpreting these patterns through the lens of heuristic processing in algorithmic contexts, this research proposes practical recommendations for scientific journals in short video creation.